The investigation of quality of power-transistor crystals soldering by a transient impedance-spectrometer - Turtsevich, A. S.; Rubtsevich, I. I.; Solov’yov, Ya. А.; Vas’kov, O. S.; Kononenko, V. K.; Niss, V. S.; Kerentsev, A. F. (Technology and design in electronic equipment, 2012)
Differential distribution profiles of the thermal «junction-to-case» resistance of KP723G transistors in accordance with the attachment of the crystals into the package have been investigated. Spectra of thermal resistances were calculated from the analysis of the temporal dependence of the dynamic thermal impedance obtained by a new non-destructive method of differential spectroscopy. The dependence of internal thermal resistance of transistor structure components on the thermal relaxation time constant is presented.